C4d deposition in early renal allograft protocol biopsies - Koo, Dicken D H; Roberts, Ian S D; Quiroga, Isabel; Procter, Jeanette; Barnardo, Martin C N M; Sutton, Margaret; Cerundolo, Lucia; Davies, David R; Friend, Peter J; Morris, Peter J; Fuggle, Susan V (Transplantation, 2004)
Deposition of the complement protein C4d in renal allograft biopsies obtained during graft dysfunction and rejection has been proposed to be a sensitive marker of antibody-mediated acute rejection. To determine the diagnostic specificity of C4d deposition, it is important to study biopsies from allografts with no evidence of dysfunction. In this study, we examined C4d deposition in protocol biopsies obtained irrespective of clinical status. Immunohistochemistry for C4d was performed on routine protocol biopsies preimplantation and on day 7 posttransplantation from 48 unselected renal allografts. Serum samples obtained up to 1 month after transplantation were assayed for donor-reactive antibodies (DRA). Results were correlated with histopathology and clinical outcome measures. Diffuse C4d deposition was detected in the peritubular capillaries of 6 of 48 (13%) biopsies. C4d deposition was present in 5 of 15 (33%) biopsies that showed acute rejection (Banff 97, category 4) but only in 1 of 33 (3%) biopsies with no rejection (P=0.003, 97% specificity). Posttransplant DRAs were detected in 21 of 48 (44%) patients. All five recipients with C4d deposition and rejection had posttransplant DRA; the recipient whose biopsy showed C4d positivity, but not rejection, did not have detectable DRA. C4d deposition was not treated with plasmapheresis or intravenous immunoglobulin and was not associated with poor posttransplant graft outcome at 1-year follow-up. Our results show that in early posttransplant protocol biopsies, C4d is a specific marker for the presence of humoral rejection, as indicated by its association with DRA and acute histologic rejection.